After ideocracy and civil society Gellner, Polanyi and the new peripheralization of Central Europe - Hann, Chris (Thesis Eleven, 2015)
Behind only that of Bronislaw Malinowski, the influence of the Central European polymaths Ernest Gellner and Karl Polanyi on socio-cultural anthropology in the 20th century was profound. Gellner and Polanyi also influenced much wider swathes of scholarship. They belong to different generations and were raised in quite different settings in Prague and Budapest respectively. What these thinkers have in common is a philosophy of history which posits the industrial revolution in northwest Europe as a radical rupture in Weltgeschichte. Polanyi’s ‘great transformation’, with its focus on the economy, corresponds to Gellner’s metaphor of the ‘big ditch’ and focus on a new polity. The cultural homogenization of the nation-state and the disembedding of the economy from society in the era of free trade are two sides of the same coin. This paper argues that these complementary models derive to a considerable degree from the scholars’ background on the margins of industrializing Europe, in the ruins of the Habsburg Empire.
Anthropology
Keywords: Central Europe; GELLNER; Ernest; anthropology; civil society

Goody, Polanyi and Eurasia: An Unfinished Project in Comparative Historical Economic Anthropology - Hann, Chris (History & Anthropology, 2015)
Goody's essay overlaps with his recent work on the “search for metals” and, more generally, with his many books expounding the commonalities of Eurasian history. His critique of Eurocentrism remains invaluable. This review article argues that his emphasis on diffusion can be usefully supplemented with a concept of civilization, to facilitate comparative structural analysis. Goody's perspective might also be enhanced by an engagement with the literature on “Axial Age” cosmologies and with substantivist economic anthropology. It is worth revisiting Karl Polanyi's efforts to grasp the position of the economy in society, in order to recover in the neoliberal present the long-run Eurasian dialectic between redistribution and market exchange.
Anthropology
Keywords: Eurasia; GOODY; Jack; 1919-2015; civilization; culture diffusion; economic anthropology

A Concept of Eurasia - Hann, Chris (Current Anthropology, 2016)
To imagine Europe and Asia as constituting equivalent "continents" has long been recognized as the ethnocentric cornerstone of a Western, or Euro-American, world view. The amalgam Eurasia corrects this bias by highlighting the intensifying interconnectedness of the entire landmass in recent millennia. This article builds on the work of Jack Goody and others to analyze the unity-in-civilizational-diversity of the Old World. It draws on the substantivist economic anthropology of Karl Polanyi to postulate continuities between ancient ideals of economic embeddedness in the agrarian empires and various forms of socialism in the twentieth century. Today, when the human economy everywhere is again exposed to the domination of the market, the Eurasian dialectic has universal relevance. However, recognition and realization of pan-Eurasian affinities continues to be impeded by geopolitics, and sociocultural anthropology has a long way to go to overcome its Atlantic bias.
Anthropology
Keywords: Eurasia; GOODY; Jack; 1919-2015; economic anthropology; ethnocentrism; geopolitics; socialism; substantivist

The Anthropocene and anthropology - Hann, Chris (European Journal of Social Theory, 2017)
Noting a lack of consensus in the recent literature on the Anthropocene, this article considers how social anthropologists might contribute to its theorizing and dating. Empirically it draws on the author’s long-term fieldwork in Hungary. It is argued that ethnographic methods are essential for grasping subjectivities, including temporal orientations and perceptions of epochal transformation. When it comes to historical periodization, however, ethnography is obviously insufficient and proposals privileging the last half-century, or just the last quarter of a century, seem inadequate. Influential theories, which define ‘modernity’ in terms of developments emanating from the countries of the North Atlantic in the sixteenth to the nineteenth centuries (Gellner, Polanyi, Wolf), remain partial and Eurocentric. To comprehend the social preconditions of the Anthropocene in a holistic fashion (the crucial contribution of comparative anthropology), it is necessary to follow Jack Goody and trace how the urban revolutions of the Bronze Age united Eurasia through the diffusion of new forms of economy, polity and cosmology.
Anthropology
Keywords: Eurasia; GOODY; Jack; 1919-2015; Hungary; anthropocene; anthropocene epoch; anthropology; cosmology; ethnology; social anthropology; socialism

Ritual and Economy: From Mutual Embedding to Non-Profit Festivalisation in Provincial Hungary - Hann, Chris (Ritualas ir ekonomika: nuo abipusės nesuprekintos ekonomikos iki nevyriausybinės festivalizacijos provincinėje Vengrijoje., 2018)
'No human beings, at whatever stage of culture, completely eliminate spiritual preoccupations from their economic concerns' (Malinowski 1935: xx). Drawing on the history and theory of economic anthropology from the pioneering investigations of Bronislaw Malinowski to the work of a postdoctoral research team at the Max Planck Institute for Social Anthropology (Halle/S) between 2009 and 2012, this paper* explores the interface between ritual and the economy in socialist and post-socialist Eastern Europe. The ruptures of early socialism gave way to a re-embedding of the economy that was especially dynamic in the sphere of the household. By contrast, postsocialist disembedding is proving harder to modify. (English)
Anthropology
Keywords: (at)kerėjimas; (dis)enchantment; (po-)socializmas; (post-)socialism; Eastern Europe; Karlas Polanyi; MALINOWSKI; Bronislaw; 1884-1942; POLANYI; Karl; 1886-1964; economic anthropology; ekonomikos nesuprekinimas; ekonominė antropologija; embeddedness; ritual; ritualas; social anthropology; socialism

Cucumbers and Courgettes: Rural Workfare and the New Double Movement in Hungary - Hann, Chris (Intersections. East European Journal of Society and Politics, 2016)
The paper is an application of the economic anthropology of Karl Polanyi to contemporary rural Hungary. After addressing the influence of Polanyi’s critique of market society and his standing in the discipline of anthropology, the main focus is the community of Tázlár on the Danube-Tisza interfluve. The paper traces the history of the ‘fictitious commodities’ of land and labour in this relatively isolated settlement, which was not fully integrated into the national society until the socialist era. The innovative symbiosis of household and cooperative farming was destroyed in the 1990s. In the depressed economic climate of today, workfare schemes are popular because they treat villagers as human beings rather than as commodities to be exploited for maximum profit. The workfare initiatives of populist power holders can be interpreted as one facet of a complex ‘double movement’ in which postsocialist society seeks to defend itself against the domination of the market.
Publisher: MTA Társadalomtudományi Kutatóközpont Kisebbsegkutató Intézet
Keywords: (post)socialism; Danube-Tisza interfluve; Hungary; Karl Polanyi; double movement; fictitious commodities; neoliberalism; workfare

Repatriating Polanyi: Market Society in the Visegrad States - Hann, Chris (Central European University Press, 2019)
Karl Polanyi’s “substantivist” critique of market society has renewed topicality in the era of neoliberal globalization. Polanyi (1886–1964) is popular among critical theorists and radical political economists, but also with ecological activists, anti-globalization campaigners and all who sense that ongoing financial turmoil is symptomatic of a deeper crisis threatening the compatibility of capitalism and democracy. The author reclaims the polymath Karl Polanyi for contemporary anthropology, especially economic anthropology. The book furthermore takes his ideas back to Central Europe, where he grew up. The Polanyian approach is applied to the communist economy, with particular reference to the “market socialist” economy which evolved under János Kádár in Hungary. The same lens is used to investigate the consequences of the demise of communist power since 1990, primarily on the basis of ethnographic investigations in Hungary and South-East Poland. Stretching the discussion on Polanyi’s great transformation – for which there is considerable international interest – in the context of neoliberalization onto the concept of Eurasia, and then bringing this into conversation with the rise of neo-nationalism in Hungary and Poland and beyond as the form that the great transformation is currently taking in the region, relates Hann’s work powerfully to the current political turbulence.
Anthropology; Political Science
Keywords: Hungary; Poland; communist economy; economic history; market socialist economy; neo-nationalism; political economy

Embeddedness and Effervescence: Political Economy and Community Sociality through a Century of Transformations in Rural Hungary - Hann, Chris (Ethnologie française, 2017)
S’appuyant sur un travail de terrain de longue haleine dans un village de la grande plaine hongroise, l’auteur analyse les liens entre économie politique et formes de sociabilité communément englobées sous le terme de rituel. Trois cycles d’intégration et de désintégration sont décrits. Chacune des phases de déstructuration a conduit à de nouvelles formes d’« auto‑protection » (Karl Polanyi) et à la construction de nouvelles relations communautaires. Les formes exemplaires de sociabilité aujourd’hui sont sensiblement différentes de celles de l’ère socialiste.
Anthropology
Keywords: (post)socialisme; Populisme; Rituel; anthropologie économique; economic anthropology; embeddedness; populism; post-socialism; ritual

Market and Society: The Great Transformation Today - Hann, Chris; Hart, Keith (Cambridge University Press, 2009)
Karl Polanyi's 1944 book, The Great Transformation, offered a radical critique of how the market system has affected society and humanity since the industrial revolution. This volume brings together contributions from distinguished scholars in economic anthropology, sociology and political economy to consider Polanyi's theories in the light of circumstances today, when the relationship between market and society has again become a focus of intense political and scientific debate. It demonstrates the relevance of Polanyi's ideas to various theoretical traditions in the social sciences and provides perspectives on topics such as money, risk, work and the family. The case studies present materials from around the world, including Britain, China, India, Jamaica and Nigeria. Like Polanyi's original work, the critical engagement of these essays will be of interest to a wide readership.
Anthropology; History
Keywords: anthropology - general; business & economics; economic history; economic theory; sociology - general

Economic Anthropology - Hann, Chris; Hart, Keith (Polity, 2011)
This book is a new introduction to the history and practice of economic anthropology by two leading authors in the field. They show that anthropologists have contributed to understanding the three great questions of modern economic history: development, socialism and one-world capitalism. In doing so, they connect economic anthropology to its roots in Western philosophy, social theory and world history. Up to the Second World War anthropologists tried and failed to interest economists in their exotic findings. They then launched a vigorous debate over whether an approach taken from economics was appropriate to the study of non-industrial economies. Since the 1970s, they have developed a critique of capitalism based on studying it at home as well as abroad. The authors aim to rejuvenate economic anthropology as a humanistic project at a time when the global financial crisis has undermined confidence in free market economics. They argue for the continued relevance of predecessors such as Marcel Mauss and Karl Polanyi, while offering an incisive review of recent work in this field. Economic Anthropology is an excellent introduction for social science students at all levels, and it presents general readers with a challenging perspective on the world economy today.Selected by Choice as a 2013 Outstanding Academic Title
Anthropology
Keywords: cultural anthropology; economic anthropology; social anthropology; sociology - general

Neoliberal Capitalism and Visegrád Countermovements - Hann, Chris; Scheiring, Gábor (Europe-Asia Studies, 2021)
Area Studies; Anthropology
Keywords: countermovement; populism; visegrad countries